2014
DOI: 10.1111/jgs.12936
|View full text |Cite
|
Sign up to set email alerts
|

The Mini‐Mental State Examination, Clinical Factors, and Motor Vehicle Crash Risk

Abstract: In a population of frequent drivers, the MMSE does not predict MVCs. Other clinical factors have a stronger association with MVC risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…The two other studies reported modestly greater risk of a crash‐related injury after a fall that may have been due to chance (summary risk estimate = 1.34, 95% CI = 0.94–1.92; Q = 0.11, P = .74; I 2 = 0%) (Figure ). The other study reported a significant association between a fall in the prior year and death or hospitalization resulting from a MVC in which the subject was driving (adjusted hazard ratio = 3.12, 95% CI = 1.71–5.69).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The two other studies reported modestly greater risk of a crash‐related injury after a fall that may have been due to chance (summary risk estimate = 1.34, 95% CI = 0.94–1.92; Q = 0.11, P = .74; I 2 = 0%) (Figure ). The other study reported a significant association between a fall in the prior year and death or hospitalization resulting from a MVC in which the subject was driving (adjusted hazard ratio = 3.12, 95% CI = 1.71–5.69).…”
Section: Resultsmentioning
confidence: 94%
“…Figure shows the numbers of records identified, screened, and retrieved in full text and the number of studies determined to meet inclusion criteria. All 15 eligible studies were published English‐language journal articles, including 10 cohort studies, two case‐control studies, and three cross‐sectional studies (Supplementary Table ) . One study each was conducted in Canada, France, and 40 countries and the rest in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, practice parameters provided by the American Academy of Neurology propose the use of global cognitive measures such as the MiniMental Status Examination (MMSE) and the Clinical Dementia Rating Scale (CDR), and a family/caregiver questionnaire of driving history, for identifying patients at risk of unsafe driving (Iverson et al, 2010), with only slightly different protocols suggested by other groups (Canadian Medical Association, 2006;Australian and New Zealand Society for Geriatric Medicine, 2010). Critically, most recommended measures are either not validated against on-road performance, or have poor evidence of association with driving safety risk (Odenheimer et al, 1994;Reger et al, 2004;Crizzle et al, 2012;Joseph et al, 2014). Furthermore, recommendations are not consistent, with some guidelines suggesting a diagnosis of early dementia is sufficient to enforce driving retirement (Iverson et al, 2010;Austroads, 2012), while others suggest this is not sufficient evidence for license cancellation (Australian and New Zealand Society for Geriatric Medicine, 2010).…”
Section: Clinical Judgment Of Driving Capacity Without Objective Assementioning
confidence: 99%
“…For example, a large Canadian study (n = 17,538) found that the MMSE did not predict crashes over two years of follow-up (Joseph et al, 2014). Generic tools and dementia screening instruments do not assess the specific deficits that cause drivers to become unsafe.…”
Section: Cognitive Functionmentioning
confidence: 99%